Case Study on Moolakabeejadi Lepa in Dadru Kushta - Kusum Mahajan; Yasmeen A. Phaniband (AYUSHDHARA, 2021)
In recent years; there has been a considerable increase in the incidence of skin problems in the developing countries like India and tropical countries due to less immunity, unhygienic, living conditions, and nutrition. The most exposed part of the body is skin. In cosmetic point of view patient who suffers with any skin diseases leads to experience physical, emotional and socio-economic embarrassment in his/her society because mirror that reflects internal & external pathology in such diseases is skin which helps in diagnosis. In among the various skin infections tinea/ringworm is one which is spreading rapidly and affecting all the age group of population. Skin infection is termed as Twak Vikara or Kushta roga in Ayurveda. In among the Kushta Roga, Dadru termed as a Dadru Kushta. In contemporary medicine, tinea/ringworm which is skin fungal infection is correlated to Dadru Kushta due to similarities in their signs and symptoms. Large community prevalence studies have demonstrated that between 20-30% of the population have various skin problems requiring attention. Present study was conducted on diagnosed patients of Dadru Kushta in patients Moolakabeejadi Lepa was applied. The drugs used in the formulations having Kandughana, Kushtahara, Krimighna, Shodhana and Tridoshahara in their properties. The results revealed highly significant effect of Moolakabeejadi Lepa in various subjective and objective parameters like Raga, Kandu and number of Pidika, number of Mandala after treatment. During follow up period of 15 days the drug effect suggested the sustained effect on the disease.